LEGO ideas on the go - Dolan, Hannah (DK Publishing, 2023)
"Explore the world with your LEGO bricks--whether it is a trip to the park, an epic camping weekend, or your dream family vacation. Bring your LEGO bricks along for the ride or use them to imagine a LEGO vacation"--